„This ash was a scholarly girl”: Műfaji és mediális fordítás Anne Carson Nox című művében - Kárpáti, Bernadett (Studia Litteraria, 2022)
In my paper, I analyse Anne Carson’s work Nox, in which the author juxtaposes her own tragic experience of grief with her philological work on Catullus’ Poem 101. Carson presents these two types of works (i.e., mourning and translation/adaptation) as parallel but ambiguous efforts to make present what has been lost and to give voice to the voiceless. After an interpretation of the Catullus poem, I will illustrate Carson’s understanding and practices of translation through a few examples and then describe the specific realization of the fundamental tension inherent in the genre of the elegy (the grasping of the mourned other and the possibilities of one’s own poetic utterance), and the reinterpretation of the dynamics of Catullus’ relationship with his sibling.